An Analysis Of Post-Relocation Adaptation Among Displaced Residents From An Urban Politics Perspective: A Case Study Of The Relocation Of TPU Kebon Nanas Residents To Pulo Gebang Rusunawa - Dear Filzah Nurhaeni; Danis Tri Saputra (UNIVERSITAS PAKUAN, 2026)
The problem of slum settlements in urban areasencourage the DKI Jakarta government to implement a relocation policy, including for residents living in the Kebon Nanas Public Cemetery (TPU) area. A total of 103 families were relocated to the Pulo Gebang Flats based on the Instruction of the Regional Secretary of DKI Jakarta Province Number 89 of 2025 as an effort to restore the function of the cemetery land. This study aims to analyze the economic, social, and cultural adaptation of the residents of TPU Kebon Nanas after the relocation from an urban politics perspective. The method used is descriptive qualitative with data collection techniques in the form of semi-structured interviews, non-participant observation, and documentation. The results of the study indicate that the relocation process took place in a top-down manner with minimal space for citizen participation, thus triggering resistance in the form of protests and walkouts. Post-relocation, residents face adaptation challenges, especially the loss of the economic ecosystem that has been formed over many years.In social and cultural aspects, residents experience changes in interaction patterns and social norms due to the move from horizontal to vertical housing, however, social networks are still maintained through joint activities.This study uses the urban politics theoretical framework of David Harvey and Mike Davis to read the structural conditions underlying residents' adaptation experiences.